OsQHB Improves Salt Tolerance by Scavenging Reactive Oxygen Species in Rice - Zhou, Jiahao; Qiao, Jinzhu; Wang, Juan; Quan, Ruidang; Huang, Rongfeng; Qin, Hua (Frontiers in Plant Science, 2022)
Soil salinity is a major environmental stress that restricts the growth and yield of crops. Mining the key genes involved in the balance of rice salt tolerance and yield will be extremely important for us to cultivate salt-tolerance rice varieties. In this study, we report that a WUSCHEL-related homeobox (WOX) gene, quiescent-center-specific homeobox (OsQHB), positively regulates yield-related traits and negatively regulates salt tolerance in rice. Mutation in OsQHB led to a decrease in plant height, tiller number, panicle length, gain length and grain width, and an increase in salt tolerance. Transcriptome and qPCR analysis showed that reactive oxygen species (ROS) scavenging-related genes were regulated by OsQHB. Moreover, the osqhb mutants have higher ROS-scavenging enzymes activities and lower accumulation of ROS and malondialdehyde (MDA) under salt stress. Thus, our findings deepen our understanding of the role of rice WOX gene family in rice development and salt tolerance, and suggest that OsQHB is a valuable target for improved rice production in environments characterized by salt stress.